2022
DOI: 10.1039/d2dt03175b
|View full text |Cite|
|
Sign up to set email alerts
|

Synthesis and evaluation of photocatalytic and photoluminescent properties of Zn2+-doped Bi2WO6

Abstract: This study consists of the synthesis of zinc-doped Bi2WO6 obtained by the sonochemical method. The XRD results indicated that the samples showed an orthorhombic phase with the P21ab space group...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
2
1
Order By: Relevance
“…Among the Bi 2−x Zn x WO 6+δ samples, 2.5 at% Zn 2+ -substituted Bi 2 WO 6 is more effective in absorbing visible light, which is important for enhancing the visiblelight-driven photocatalytic activity. Unlike in previous studies, 38,55,56 no background absorption beyond the absorption edges was observed upon partial substitution of Zn 2+ , suggesting the absence of deep impurity states within the band gap.…”
Section: Materials Characterizationcontrasting
confidence: 78%
See 1 more Smart Citation
“…Among the Bi 2−x Zn x WO 6+δ samples, 2.5 at% Zn 2+ -substituted Bi 2 WO 6 is more effective in absorbing visible light, which is important for enhancing the visiblelight-driven photocatalytic activity. Unlike in previous studies, 38,55,56 no background absorption beyond the absorption edges was observed upon partial substitution of Zn 2+ , suggesting the absence of deep impurity states within the band gap.…”
Section: Materials Characterizationcontrasting
confidence: 78%
“…Recently, Lovisa et al 55 experimentally studied the impact of partial substitution of Zn for Bi on the photocatalytic and photoluminescence properties of Bi 2 WO 6 and found that Zn could not effectively favor the photocatalytic property but the photoluminescence property due to the increase in the recombination rate of photoexcited charge carriers in the oxygen vacancy-related defects. On the contrary, In 2 O 3 nanostructures with pores showed high photocatalytic activity toward PFAS degradation because of the presence of abundant oxygen vacancy defects on their surface, 30 which received an O atom from the –COOH group of PFOA molecules, forming a close contact with In 2 O 3 and improving the charge transfer and photocatalytic activity under UV irradiation.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, iron doping displayed a plasmonic resonance effect and consequently a strong absorption of visible light was noted. 122 In a related study, Lovisa et al , 123 reported the manufacture of zinc-doped Bi 2 WO 6 . In this study they demonstrated that increasing the Zn 2+ concentration promoted the inhibition of photocatalytic characteristics through the occurrence of oxygen vacancies that functioned as a charge recombination center.…”
Section: Photocatalytic Propertiesmentioning
confidence: 99%